Recent Trends In Mosque Management - Fahmi, Rizqi Anfanni (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
This research explores the evolving role of mosques in contemporary society, particularly focusing on their functions beyond religious observance. The purpose is to examine the various aspects of mosque management, including disaster response, community engagement, health initiatives, financial sustainability, and environmental stewardship. Using a qualitative approach, the study analyzed literature collected from Scopus database, emphasizing articles published between 2015 and 2025. Findings indicate that mosques have significantly expanded their influence, transforming into key community hubs. They are increasingly recognized for fostering social cohesion through educational programs, health initiatives, and economic empowerment activities. In response to the COVID-19 pandemic, mosques adapted quickly by implementing health protocols and providing essential services, thus reinforcing their role in public health management. Additionally, the research highlights the importance of transparent financial practices and the integration of environmental sustainability efforts in mosque operations. The implications of these findings suggest that mosques, when effectively managed, can enhance community resilience, promote socio-economic development, and contribute to environmental sustainability. Future research should investigate the long-term impact of mosque-based programs on community well-being and explore strategies for overcoming barriers such as limited resources and resistance to change. By embracing these roles, mosques can continue to serve as pillars of support and transformation within their communities.